2022
DOI: 10.26502/acbr.50170221
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Micronutrients against COVID-19

Abstract: Background and Objectives: There is no pharmacological treatment with proven e cacy against coronavirus disease-19. Certain micronutrients have roles in the maintenance of an effective immune system. From the point of view of public health, it will be good to adopt a nutrional strategy to enhance the immunity of the general population against viral diseases.Method and Study design: A review was done to now the evidence for the antiviral and immunomodulatory properties of micronutrients. A search was done in Pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In this study, IgG response in BALB/c mice was determined serologically using indirect ELISA and the observed higher mean OD 450nm values for selenium-supplemented against the non-supplemented groups over the 28-day immunization period support the report that selenium does boost production of anti-spike IgG antibody [ 24 ]. However, another study found no correlation between selenium status or intake, and SARS-CoV-2 anti-spike IgG antibody response [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, IgG response in BALB/c mice was determined serologically using indirect ELISA and the observed higher mean OD 450nm values for selenium-supplemented against the non-supplemented groups over the 28-day immunization period support the report that selenium does boost production of anti-spike IgG antibody [ 24 ]. However, another study found no correlation between selenium status or intake, and SARS-CoV-2 anti-spike IgG antibody response [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
“…Their supplementations reduced the progression of HIV disease and the incidence of HIV-associated complications in infected women [89] as well as mortality in patients with Ebola virus disease [90]. The success with other viral infections has led to the proposal to use them in the treatment of COVID-19 patients [87,91]. These micronutrient supplements also reduced the incidence of clinical malaria [92,93], improved anti-malarial parameters and survival [94] and improved recovery in influenza [95].…”
Section: Micronutrient Supplements For Communicable and Non-communica...mentioning
confidence: 99%